Comparison of PT and aPTT Results in Icteric Samples using Optical and Electromechanical Methods - Ria Zulfa; Dewi Indah Sari Siregar; Nelly Elfrida Samosir; Ricke Loesnihari; Ranti Permatasari; Sylvia Youvella (Indonesian Journal of Global Health Research, 2026)
Prothrombin time (PT) and activated partial thromboplastin time (aPTT) tests are important screening tests for assessing coagulation pathway function and monitoring anticoagulant therapy. These tests use a coagulation analyzer with different detection methods, namely optical and electromechanical methods. The working principles of the two methods can cause variations in test results, especially in samples with icteric interference. Therefore, it is necessary to evaluate the comparison of PT and aPTT values in icteric samples using both methods.  This study aimed to evaluate the differences in PT and aPTT values in icteric samples using optical and electromechanical methods. This study used a prospective analytical design with a cross-sectional approach, conducted at Adam Malik Hospital, Medan, from July to August 2025. A total of 69 samples that met the inclusion criteria were selected using sequential sampling techniques. Each sample is tested for PT and aPTT using optical and electromechanical methods. The results of each test were analyzed using the Mann-Whitney, Kappa, correlations tests, and Bland-Altman plots. Significant differences were observed in PT and aPTT values between the optical and electromechanical methods (p<0.001), while INR values showed no significant difference (p=0.426). Interpretation agreement was moderate for PT (κ=0.599; p<0.001) and strong for aPTT (κ=0.661; p<0.001). Despite numerical differences, both methods provided comparable clinical interpretations, and total bilirubin showed no association with PT or aPTT values. The optical and electromechanical methods produced comparable clinical interpretations despite differences in PT and aPTT values, and total bilirubin levels were not associated with PT or aPTT results.